Molecular Characterization of Reduced Susceptibility to Biocides in Clinical Isolates of Acinetobacter baumannii - Lin, Fei; Xu, Ying; Chang, Yaowen; Liu, Chao; Jia, Xu; Ling, Baodong (Frontiers in Microbiology, 2017)
Active efflux is regarded as a common mechanism for antibiotic and biocide resistance. However, the role of many drug efflux pumps in biocide resistance in Acinetobacter baumannii remains unknown. Using biocide-resistant A. baumannii clinical isolates, we investigated the incidence of 11 known/putative antimicrobial resistance efflux pump genes (adeB, adeG, adeJ, adeT1, adeT2, amvA, abeD, abeM, qacE, qacEΔ1 and aceI) and triclosan target gene fabI through PCR and DNA sequencing. Reverse transcriptase quantitative PCR was conducted to assess the correlation between the efflux pump gene expression and the reduced susceptibility to triclosan or chlorhexidine. The A. baumannii isolates displayed high levels of reduced susceptibility to triclosan, chlorhexidine, benzalkonium, hydrogen peroxide, and ethanol. Most tested isolates were resistant to multiple antibiotics. Efflux resistance genes were widely distributed and generally expressed in A. baumannii. Although no clear relation was established between efflux pump gene expression and antibiotic resistance or reduced biocide susceptibility, triclosan non-susceptible isolates displayed relatively increased expression of adeB and adeJ whereas chlorhexidine non-susceptible isolates had increased abeM and fabI gene expression. Increased expression of adeJ and abeM was also demonstrated in multiple antibiotic resistant isolates. Exposure of isolates to subinhibitory concentrations of triclosan or chlorhexidine induced gene expression of adeB, adeG, adeJ and fabI, and adeB, respectively. A point mutation in FabI, Gly95Ser, was observed in only one triclosan-resistant isolate. Multiple sequence types with the major clone complex, CC92, were identified in high level triclosan-resistant isolates. Overall, this study showed the high prevalence of antibiotic and biocide resistance as well as the complexity of intertwined resistance mechanisms in clinical isolates of A. baumannii, which highlights the importance of antimicrobial stewardship and resistance surveillance in clinics.